Basic concepts of maritime transport and its present status in Latin America and the Caribbean - Whittle, Tomas Sepulveda (ECLAC SantiagoCL, 1987)
Outlines the importance, needs and structure of the shipping industry, the current situation in this sector at world and regional levels, and the factors that influence its development. Discusses shipping concepts including ships, cargo, and ports. Reviews the Code of Conduct for Liner Conferences. Considers related maritime transport topics including , inter alia, freight rates, transport conditions, marine insurance, open registry flags, cargo unitization, multimodal transport, shipping policy and international organizations and maritime transport.